Redistribution of tractive force per axle for electric locomotives with asynchronous traction motors - N. D. Shilin; S. N. Prokof'ev (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. Improving the traction and adhesion properties of freight electric locomotives is currently an urgent issue for the domestic locomotive industry. The increase in the mass and speed of trains enables to seek new ways and possibilities for realising the maximum tractive force of freight locomotives in order to meet the requirements of the rapidly developing transportation methods.Materials and methods. The authors carries out the analysis of existing theoretical and practical methods of adhesion control and developed the algorithm for controlling the wheelsets adhesion of a locomotive with asynchronous traction motors.Results. The authors concerning the tests analysis of a real electric locomotive, developed a mathematical model of the locomotive movement, which included algorithms for axial control of the tractive force with the redistribution of the tractive force between the axles. Calculations of a mathematical model of the movement of a locomotive with a train on a section with the redistribution algorithm both enabled and disabled, as well as with various settings of this algorithm, were carried out. The model also took into account the change in the adhesion coefficient of the wheels with the rails depending on the numerical order of a wheelset in the direction of travel, as well as the additional loading and unloading forces that arise in the undercarriage depending on the tractive force being realised. As a result of the calculations, obtained data showed good convergence with the test data of a real electric locomotive.Discussion and conclusion. The developed mathematical model allows evaluating the realisation of the tractive force of a locomotive as close as possible to that specified by the locomotive throttle under conditions of a changing adhesion coefficient and its heterogeneity under different wheelsets of the locomotive. The obtained results can be further applied in the development of promising freight electric locomotives with asynchronous traction motors.